Integrated chemical looping gasification and steam reforming of palm oil waste for green hydrogen production in Indonesia: A comprehensive analysis and Aspen Plus simulation - Muchammad Ilham Najib; Dhea Wahyu Amanda Arifin (Journal of Innovation Materials, Energy, and Sustainable Engineering, 2026)
Background: Indonesia accounts for 42% of global palm oil production, generating 60 million tons of biomass waste per year, mainly empty fruit bunches and palm kernel shells that have strong potential to be converted into hydrogen (H2) through biomass gasification as a renewable energy transition. This is relevant given that national hydrogen demand is projected to reach 6,282 TWh by 2060. Integrated chemical looping gasification technology with steam reforming using oxygen carrier NiFe2O4 shows promise for green hydrogen production from palm oil waste. Methods: This study was conducted through a literature review for comprehensive analysis and simulation data fulfillment. Process simulations were performed and analyzed using Aspen Plus, and sensitivity analysis was conducted for process optimization. Findings: Simulation results hydrogen production reaching 82.77 kg/hour at a gasification temperature of 700℃ and a steam-to-biomass ratio of 0.9 with H2 selectivity reaching 54.43%. Assessment of raw material quality and H2 production quality revealed a material utilization rate of 12.08 tons per ton of H2 produced. This simulation confirms the importance of optimizing the gasification temperature and steam-to-biomass ratio to produce high-quality syngas. PESTEL analysis shows that the use of palm oil waste for hydrogen has high economic value and creates a positive social impact. From a legal and environmental perspective, this conversion is in line with emission reduction regulations, making it feasible and highly implementable. Conclusion: Hydrogen production from palm oil waste using chemical looping gasification and steam reforming processes has significant potential for renewable energy in Indonesia. Novelty/Originality of this article: This study contributes by integrating technical, environmental, and socio-economic aspects in the analysis of hydrogen production from palm oil waste. Unlike most literature that focuses solely on process performance or technical aspects, this study combines Aspen Plus-based process simulation with PESTEL evaluation to assess the overall feasibility of the technology.